Conceptual Approaches to the Development of Economic Systems in the Context of Globalization and Regionalization - D. I. Kolomyychuk (Scientific Bulletin of the National Academy of Statistics, Accounting and Audit, 2017)
Interactions o f the national and the global in economic transformations occurring in open economic systems are substantiated. Conceptual approaches to the development o f economic systems in the globalization and regionalization context are summed up. It is shown that globalization is a logical consequence o f mutual influences and interactions o f multiple local transformations in socio-economic systems o f various levels, which planetary self-organization generates the new quality o f the global economic development. It is concluded that globalization has controversial impact on the transformation capacities o f national economic systems that have to operate in the unfavorable condition o f the growing instability o f the global economic system and rapid integration in the structures with already established economic relations. The heuristic and experimental nature o f economic and institutional transformations in these countries is added by splits of national economic systems and disruptions o f established production links; the outstripping liberalization o f foreign economic relations, creating rather external than internal pressures on national manufacturers and making them less capable to adapt to the competitive environment; the accelerated liberalization o f monetary andfinancial systems, opening up ways to reallocation o f capital from the sluggish real sector to the more flexible sector o f transactions with currencies and securities; the shrinking regulatory authorities o f national governments with respect o f trade, competition, tax policies or social welfare; the growing domination ofTNC and outflow o f productive resources from national economies, important for their self-development, thus making their economic systems structurally primitive; the sharp property differentiation within societies and the increasing shares o f population with low incomes.